PENYULUHAN HIPERTENSI DAN DIABETES MELITUS PADA MASYARAKAT DESA CARINGIN, LEGOK, KABUPATEN TANGERANG - Karnelasatri Karnelasatri; Andriyani Andriyani; Febbyasi Megawati; Yovita Diane Titiesari; Fany Febriani; Kevin Adithya Beda (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Community Service activities in Caringin Village, Legok, were carried out through a series of activities including healthy exercises, health education, and free mini medical checkups. This program was conducted in collaboration with the Caringin Community Health Center, where educational materials on hypertension and diabetes mellitus (DM) were presented by doctors in the form of presentations, discussion, and health consultations. In addition, educational materials were also distributed via leaflets to reach residents who did not fully participate in the activities. The resident understanding was evaluated through pre- and post-tests, while activity implementation was evaluated through a satisfaction survey. The results of the free mini medical check-ups showed a high prevalence of hypertension, with 76% of residents having systolic blood pressure above 120 mmHg and 38% of them falling into the hypertension category of ≥140 mmHg. In addition, 17% of residents had blood sugar levels above normal, with 7% requiring further examination. The results of the evaluation of residents' understanding showed an average increase of 7%, while the satisfaction survey showed that the majority of residents were satisfied with the implementation of the activities (>90%). Some of the obstacles encountered were discrepancies in the number of participants who took the pretest and post-test, as well as misinterpretation of the pretest and post-test questions by residents, especially the elderly. However, this activity provided an overview of the effectiveness of an integrative approach to health education in raising awareness in the community and detecting early disease risks. Moreover, collaboration with local health service units provided opportunities for data-based follow-up on the results of the activity.